2006
DOI: 10.1038/nature04368
|View full text |Cite
|
Sign up to set email alerts
|

Constant darkness is a circadian metabolic signal in mammals

Abstract: Environmental light is the 'zeitgeber' (time-giver) of circadian behaviour. Constant darkness is considered a 'free-running' circadian state. Mammals encounter constant darkness during hibernation. Ablation of the master clock synchronizer, the suprachiasmatic nucleus, abolishes torpor, a hibernation-like state, implicating the circadian clock in this phenomenon. Here we report a mechanism by which constant darkness regulates the gene expression of fat catabolic enzymes in mice. Genes for murine procolipase (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
214
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(223 citation statements)
references
References 25 publications
6
214
2
1
Order By: Relevance
“…These changes may underlie cognitive impairments in patients recovering from severe hypothermia, like those demonstrated by Walpoth et al (1997) where body temperature dropped as low as 17°C for several hours. To investigate this process in a homeotherm, it would be interesting to determine whether similar microstructural changes are occurring in a mouse model of torpor (Zhang et al, 2006). More research is needed to further understand the mechanisms driving this highly malleable system, the role that this form of neural plasticity plays in the unique adaptation of hibernators to the cold, and the resulting effects of these repeated neural changes on learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may underlie cognitive impairments in patients recovering from severe hypothermia, like those demonstrated by Walpoth et al (1997) where body temperature dropped as low as 17°C for several hours. To investigate this process in a homeotherm, it would be interesting to determine whether similar microstructural changes are occurring in a mouse model of torpor (Zhang et al, 2006). More research is needed to further understand the mechanisms driving this highly malleable system, the role that this form of neural plasticity plays in the unique adaptation of hibernators to the cold, and the resulting effects of these repeated neural changes on learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…creatic lipases (Squire et al 2003). Expression analysis of the gene encoding PLRP2 demonstrated that it was coordinately expressed with procolipase (Zhang et al 2006). These observations indicated that DD-activated gene regulation is part of a complex biological program and is not unique to procolipase.…”
Section: Peripheral Organ Genes Activated By Dd Environmentmentioning
confidence: 99%
“…(Zhang et al 2006). This microarray comparison identified a gene encoding procolipase that was highly expressed in the liver from the animal kept in DD.…”
Section: Peripheral Organ Genes Activated By Dd Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 5'-AMP was recently found to serve as a circulating chemical cue that signals constant darkness and induces torpor, a hibernation-like state characterized by depressed body temperature and metabolic rate. 78,79 On the other hand, feeding mice with a high-fat diet leads to changes in free-running period, feeding behavior and clock gene expression. 80 These findings underscore the importance of nutritional cues as upstream signals that coordinate circadian clock and metabolic oscillations.…”
Section: Metabolites As Integrators Of Clock and Metabolismmentioning
confidence: 99%